Export Promotion Schemes and Export Performance in the East African Community: A Comparative Analysis - Ongeri, Benedicto Onkoba; Ongeri, Jutine Mogendi (Archives of Business Research, 2017)
This study analyzed the impact of various fiscal incentives (export promotion schemes) in the East African Community on promoting exports in the region. The schemes in place are; the manufacturing under bond scheme, export processing zones and duty remission facility for Kenya; Duty draw back scheme, excise duty relief, export processing zones and VAT exemption scheme for Tanzania; for Uganda it has duty drawback, manufacturing under bond and foreign exchange liberalization schemes. These schemes are stated in the East African Community customs union protocol, 2005. Effectively, this study was to investigate the actual impact of these schemes for each country and carry out a comparison on which ones have performed better than which ones (if actually there is any performance). Using an augmented gravity model, results showed that duty drawback scheme was the most significant export promotion scheme in promoting export volumes in EAC partner states. The results showed that duty drawback scheme boosted the volumes of exports in both Uganda and Tanzania. In Kenya duty remission facility and export processing zones were the most effective export promotion schemes in promoting the volumes of exports. Export processing zones though effective for Kenya, the results showed opposite impact for Tanzania. Manufacturing under bond scheme, though being in existent in Kenya and Uganda for a very long time, was not effective in promoting volumes of exports in both countries according to the study results. Also, Value added tax remission and excise duty relief schemes are not effective in promoting the volumes of exports in Uganda and Tanzania respectively.